The English poems of George Herbert. - Herbert, George, 1593-1633.; Patrides, C. A. (London, Dent; Totowa, N.J., Rowman and Littlefield, 1975)
This fully annotated edition of the complete English poems of George Herbert provides the text of the reliable first edition of The Temple (1633). Appended are six poems not included in The Temple, three versions of The Elixir to show Herbert's approach to revision, and several secular poems which he intentionally parodied. The edition begins with an outline of the poet's life and ends with a comprehensive twenty-five page bibliography. - Jacket.
To the reader -- An outline of Herbert's life -- A crown of praise : the poetry of Herbert -- A note on typology -- The Temple. The church-porch -- The church -- The church militant -- Appendixes. Poems not included in The Temple -- Three versions of a poem by Herbert -- Some secular poems parodied by Herbert.
George Herbert also wrote Latin poems, not included in this collection. The English poems were first published, posthumously, as: The temple. Cf. Columbia encycl.
Bibliography: p. [214]-238.
Keywords: Christian poetry, English -- Early modern, 1500-1700.